The accuracy of automated oscillometry compared to manual doppler in measuring ankle brachial index in suspected peripheral arterial disease patients: a systematic review - Achmad Ismail Sampurna Putra (DiscoverSys Inc., 2018)
Background: Golden standard to diagnose Peripheral Artery Disease (PAD) is angiography. A more common and practical alternative technique is by calculating Ankle Brachial Index (ABI) using Oscillometry as systolic blood pressure measurement. Though, its accuracy remains obscure.Methods: A systematic search was performed using PubMed and Google Scholar database.Â There were 11 articles were found after reviewed for the title and abstract by inclusion and exclusion criteria. However, only 6 articles were relevant and used by the authors.Results: Based on the six journals appraised, the sensitivity of automated oscillometry in detecting PAD (ABI <0.9) ranged from 0.4-0.7. The specificity, however, showed better result around 0.75-1. It shows that those patients who scored negative for PAD with oscillometry are not likely to have the disease. Automated oscillometry in studies appraised was also seen to have moderate positive and negative predictive value, which may indicate the possibility of this simpler diagnostic tool to be used to screen PAD. Most of the studies demonstrated good likelihood ratio for oscillometry, which even adds more power to oscillometry as a PAD diagnostic tool.Conclusion: Automated oscillometry was comparable with manual Doppler due to its high specificity. Several advantages were identified such as; oscillometry required less reliant on the specialized skills, commonly available, reliable, and simple to use which can be performed by primary care physicians even in their primitive set up. Thus, the oscillometric method can be utilized as an alternative in diagnosing patients suspected with PAD.